Three Decades of Research on Plasminogen Activator Inhibitor-1: A Multifaceted Serpin - Declerck, Paul J.; Gils, Ann (Seminars in Thrombosis and Hemostasis, 2013)
Plasminogen activator inhibitor 1 (PAI-1) is the main inhibitor of tissue-type (t-PA) and urokinase-type (u-PA) plasminogen activator and therefore plays an important role in the plasminogen–plasmin system. PAI-1 is involved in a variety of cardiovascular diseases (mainly through inhibition of t-PA) as well as in cell migration and tumor development (mainly through inhibition of u-PA and interaction with vitronectin). PAI-1 is a unique member of the serpin superfamily, exhibiting particular unique conformational and functional properties. Because of its involvement in various biologic and pathophysiologic processes, PAI-1 has been the subject of many studies, including extensive structural investigations, in vitro cell biologic studies, in vivo animal studies, and epidemiologic studies. The review provides an overview on the current knowledge on PAI-1.
Keywords: plasminogen activator inhibitor 1; PAI-1; fibrinolysis; cancer; plasminogen activation; serpin